Oxidative-Inflammatory Stress in Immune Cells from Adult Mice with Premature Aging - Antonio Garrido (International Journal of Molecular Sciences, 2019)
Oxidative and inflammatory stresses are closely related processes, which contribute to age-associated impairments that affect the regulatory systems such as the immune system and its immunosenescence. Therefore, the aim of this work was to confirm whether an oxidative/inflammatory stress occurs in immune cells from adult mice with premature aging, similar to that shown in leukocytes from chronologically old animals, and if this results in immunosenescence. Several oxidants/antioxidants and inflammatory/anti-inflammatory cytokines were analyzed in peritoneal leukocytes from adult female CD1 mice in two models of premature aging—(a) prematurely aging mice (PAM) and (b) mice with the deletion of a single allele (hemi-zygotic: HZ) of the tyrosine hydroxylase (th) gene (TH-HZ), together with cells from chronologically old animals. Several immune function parameters were also studied in peritoneal phagocytes and lymphocytes. The same oxidants and antioxidants were also analyzed in spleen and thymus leukocytes. The results showed that the immune cells of PAM and TH-HZ mice presented lower values of antioxidant defenses and higher values of oxidants/pro-inflammatory cytokines than cells from corresponding controls, and similar to those in cells from old animals. Moreover, premature immunosenescence in peritoneal leukocytes from both PAM and TH-HZ mice was also observed. In conclusion, adult PAM and TH-HZ mice showed oxidative stress in their immune cells, which would explain their immunosenescence.